An evolutionary perspective on the necroptotic pathway. Issue 10 (October 2016) - Dondelinger, Yves; Hulpiau, Paco; Saeys, Yvan; Bertrand, Mathieu J.M.; Vandenabeele, Peter
Abstract : Throughout the animal kingdom, innate immune receptors protect the organism from microbial intruders by activating pathways that mediate inflammation and pathogen clearance. Necroptosis contributes to the innate immune response by killing pathogen-infected cells and by alerting the immune system through the release of danger signals. Components of the necroptotic signaling axis – TIR-domain-containing adapter-inducing interferon-β (TRIF), Z-DNA sensor DAI, receptor-interacting kinase (RIPK)1, RIPK3 and mixed-lineage kinase domain-like protein (MLKL) – are therefore expected to be found in all animals. However, a phylogenetic analysis reveals that the necroptotic axis, except for RIPK1, is poorly conserved in the animal kingdom, suggesting that alternative mechanisms regulate necroptosis in these species or that necroptosis would apparently be absent. These findings question the universal role of necroptosis during innate immunity in the animal kingdom. Trends: Necroptosis is believed to contribute to innate immunity in humans and mice by killing pathogen-infected cells and by alerting the immune system through the release of danger signals RIPK3 and MLKL form the core machinery of necroptotic cell death in mammalian cells During necroptosis, RIPK3 phosphorylates and activates MLKL MLKL activation results in its recruitment and oligomerization at phosphatidylinositol phosphates in the plasma membrane leading to plasma membrane rupture and cell death It is unclear when the necroptotic cell death pathway emerged and whether it acts as a universal cell death program in the animal kingdom